Pengukuran Kinerja Supply Chain Management PT Otsuka Indonesia dengan Metode Supply Chain Operation Reference - Syahfarini, Zakinah Mutiara; Oktiarso, Teguh; Purnomo, Purnomo (Teknik Industri Universitas Ma Chung, 2023)
Supply chain management encompasses the study of efficiency and effectiveness in material, information, and monetary flow within the industrial sector. Assessing performance is pivotal in gauging a company's managerial capacities. At PT Otsuka Indonesia, research was undertaken during an internship, involving observations and interviews. Subsequently, Key Performance Indicators (KPIs) were formulated, covering aspects such as accuracy in raw material usage, precision in production level planning, frequency of production plan changes, source cycle time, finished product quality, make cycle time, delivery cycle time, precision in avoiding delays in finished goods delivery, and return of finished goods. Snorm de Boer normalization was applied to calculate the KPIs, generating performance results for each indicator. Determining the ultimate performance involved weighting via the Analytical Hierarchy Process (AHP) method, assigning significance levels to each KPI. Post data processing, it was evident that the finished product quality indicator had the lowest value. Consequently, improvement proposals were designed using the Failure Mode and Effects Analysis (FMEA) method. These proposals culminated in the development of warning sticker designs for machine cleaning, comprehensive Personal Protective Equipment (PPE) usage, and scales rechecking.